Scenes, Quarters and Clusters: the Formation and Governance of Creative Places in Urban China - Wen Wen (Cultural Science)
This paper presents a PhD program examining the formation and governance patterns of the social and spatial concentration of creative people and creative businesses in cities. It develops a typology for creative places, adding the terms ‘scene’ and ‘quarter’ to ‘clusters’, to fill in the literature gap of partial emphasis on the ‘creative clusters’ model as an organising mechanism for regional and urban policy.